APPLICATION OF DATA MINING TECHNIQUES TO FIND RELATIONSHIPS BETWEEN THE DISHES OFFERED BY A RESTAURANT FOR THE ELABORATION OF COMBOS BASED ON THE PREFERENCES OF THE DINERS - Rosa Maria VAZQUEZ; Edmundo BONILLA; Eduardo SANCHEZ; Oscar ATRIANO; Cinthya BERRUECOS (Applied Computer Science, 2019)
Currently, blended food has been a common menu item in fast food restau-rants. The sales of the fast-food industry grow thanks to several sales strate-gies, including the “combos”, so, specialty, regional, family and buffet restaurants are even joining combos’ promotions. This research paper presents the implementation of a system that will serve as support to elab-orate combos according to the preferences of the diners using data mining techniques to find relationships between the different dishes that are offered in a restaurant. The software resulting from this research is being used by the mobile application Food Express, with which it communicates through webservices.